Analytical and Crystallographic Parameters of Cd(II) Complexes Derived from Substituted Schiff Bases - TURWATKAR, S.L.; MEHTA, B.H. (Asian Journal of Chemistry, 2010)
Schiff base ligands were synthesized using 5-nitrosalicylaldehyde with o-toluidine, p-toluidine, o-aminobenzoic acid, p-aminobenzoic acid and 2-hydroxy-1-naphthaldehyde with o-aminobenzoic acid, p-aminobenzoic acid. Cadmium(II) complexes of these Schiff bases were synthesized having the metal:ligand stoichiometry 1:2. The Schiff bases and their metal complexes were characterized for analytical parameters and spectral features. The structures of these complexes were proposed on basis of NMR, UV-Visible, IR spectral data.